Nilai-Nilai Keadilan Dalam Hukum Adat dan Hukum Keluarga Islam Pada Masyarakat Adat Kampung Naga Tasikmalaya - Muhamad Indanus; Sugianto Sugianto (Fakultas Hukum, Universitas Warmadewa, 2024)
This research discusses the values of justice in customary law and Islamic family law implemented by the indigenous people of Kampung Naga Tasikmalaya. The Kampung Naga community has a strong customary law system, but also adheres to Islamic teachings, so there are efforts to harmonize customary law with the principles of Islamic family law. This research aims to understand the concept of justice in customary law in Kampung Naga, identify the values of justice in Islamic family law implemented in Kampung Naga, identify areas of similarities and differences between the two legal systems, and explore how the people of Kampung Naga harmonize the two in their lives. daily. Based on the research results, it was found that there is common ground in the value of justice which is achieved through cultural and religious dialogue, although some differences are maintained as a form of respect for the cultural identity of indigenous peoples.